Characterizing skin color before and after 100‐m sprinting. Issue 6 (11th May 2021) - Jiang, Li; Wang, Han; Zhang, Xiaohui; Gao, Cheng; Xiao, Kaida; Melgosa, Manuel; Li, Changjun
Abstract: We studied skin color in participants before and after a 100‐m sprint using a Konica Minolta CM‐2600d spectrophotometer. Four body positions (forehead, cheek, neck, and inner forearm) were measured for the approximately 30 students (non‐professional runners) who participated in the experiment. Skin reflectance was measured three times at each position before running and again soon afterward. Analysis of the data showed that average measurement repeatability (mean color difference from the mean [MCDM]) was 0.5, 0.4, 0.3, and 0.2 CIELAB units for forehead, cheek, neck, and inner forearm, respectively. However, average skin color differences produced by running were 1.8, 2.2, 2.0, and 1.7 CIELAB units for forehead, cheek, neck, and inner forearm positions, respectively, which are considerably higher than repeatability before or after running. Furthermore, appearance variation was analyzed in the CIELAB space, and it was found that sprinting for 100 m considerably changes the values of the red‐green a * coordinate, while the lightness L * and yellow‐blue b * coordinates remain almost constant. More specifically, on average, a * decreases after running for the forehead, cheek, and neck positions, while the opposite is true for the inner forearm position. The findings in this article may be useful to test previous physical models, achieve more realistic images of human skin after sprinting, and contribute to work of CIE TC 1‐92 on skin spectra database.